An Extremely Rare Case of Small Cell Carcinoma in Submandibular Salivary Gland - Philip, Nigi Ross (J Clin Diagn Res, 2017)
Small Cell Carcinoma (SCC) of the salivary gland is a rare and aggressive tumour accounting for about less than 1% of the salivary gland tumours. Submandibular gland involvement is extremely rare. These tumours frequently present with metastasis to lymph node and distant organs. We report a case of a 30-year-old male patient who presented with a swelling on the left side of the face below the jaw and the floor of the mouth. The tumour was excised followed by histopathological evaluation and diagnosed as SCC of left submandibular gland. Immunohistochemistry was positive for pan cytokeratin, synaptophysin, chromogranin, Ki-67, CK5/6, and negative for Thyroid Transcription Factor (TTF-1) which confirmed that the tumour was SCC of submandibular salivary gland.